A responsabilidade penal por omissão nos crimes empresariais - Aranha, Rodrigo Domingues de Castro Camargo (2018)
Since the beginning of the new millennium, the speech against impunity and corruption has gained strength in Brazilian society. Following the trend, National Courts and the persecution authorities started to realize, more often, the imputation of criminal responsibility by improper omission, without the technical care that this form requires. This work will try to bring appropriate legal remedies to this problem. In the first moment, it will be analyzed the concept of omission, the elements which composes it and we are going to compare it with the concept of action. Then, it will be presented the existing proposals for the doctrinal classification between the proper omissive crimes and the improper omissive crimes, exhibiting the differentiation criteria. Further up, it will be verified how does the causal link between the omission and the result works, considering that, in its essence, the omission is the absence of corporal movement and, therefore, the modification of the exterior world. Entering in the improper omission issue, it will be exposed the theories presented about the fundamentals of a guarantee duty, from the formal ones to the ontological ones. After that, a theorical survey related to the Corporation reality will be presented, pointing out the challenges in the application of omissive crimes theory to the facts occurred in business daily reality. Lastly, theories that are recurrently linked with the omissive crimes will be presented and it will be analyzed their relevance with this work